Implementasi Manajemen Strategik Berbasis Sekolah - Nirmayanthi, Andi; Abdalla, Mohammad Ali Fadlalla; Hasan, Mardhiah; Syamsudduha, St. (Cognoscere: Jurnal Komunikasi dan Media Pendidikan, 2024)
The implementation of School-Based Strategic Management (SBMS) aims to improve the quality of education through granting greater autonomy to schools. The implementation of SBM involves all stakeholders in the decision-making process, including the principal, teachers, students, parents and the community. This strategy focuses on managing school resources based on local potential and needs and emphasizes the active participation of all stakeholders. The strategic management process of SBM includes the formulation, implementation and evaluation of strategies that are tailored to school conditions. The successful implementation of SBM is strongly influenced by the quality of human resources, the availability of funds, adequate facilities and community support. With a flexible and sustainable approach, SBM can be an effective tool in improving the quality of education and facing challenges in an ever-evolving educational environment. Abstrak Implementasi Manajemen Strategik Berbasis Sekolah (MBS) bertujuan untuk meningkatkan mutu pendidikan melalui pemberian otonomi yang lebih besar kepada sekolah. Penerapan MBS melibatkan seluruh pemangku kepentingan dalam proses pengambilan keputusan, termasuk kepala sekolah, guru, siswa, orang tua, dan masyarakat. Strategi ini berfokus pada pengelolaan sumber daya sekolah berdasarkan potensi dan kebutuhan lokal, serta menekankan pada partisipasi aktif seluruh pihak terkait. Proses manajemen strategik MBS meliputi perumusan, implementasi, dan evaluasi strategi yang disesuaikan dengan kondisi sekolah. Keberhasilan implementasi MBS sangat dipengaruhi oleh kualitas sumber daya manusia, ketersediaan dana, fasilitas yang memadai, serta dukungan masyarakat. Dengan pendekatan yang fleksibel dan berkelanjutan, MBS dapat menjadi alat yang efektif dalam meningkatkan mutu pendidikan dan menghadapi tantangan dalam lingkungan pendidikan yang terus berkembang. Keywords: Strategik, Berbasis Sekolah, Mutu Pendidikan